Pre-task music improves swimming performance - Smirmaul, B. P. C. [UNESP]; Dos Santos, R. V.; Da Silva Neto, L. V. (Edizioni Minerva Medica, 2015)
Aim. The purpose of this study was to investigate the effects of pre-task music on swimming performance and other psychological variables. Methods. A randomized counterbalanced within-subjects (experimental and control condition) design was employed. Eighteen regional level male swimmers performed two 200-m freestyle swimming time trials. Participants were exposed to either 5 minutes of self-selected music (pre-task music condition) or 5 minutes of silence (control condition) and, after 1 minute, performed the swimming task. Results. Swimming time was significantly shorter (-1.44%) in the pre-task music condition. Listening to pre-task music increased motivation to perform the swimming task, while arousal remained unchanged. While fatigue increased after the swimming task in both conditions, vigor, ratings of perceived exertion and affective valence were unaltered. Conclusion. It is concluded, for the first time, that pre-task music improves swimming performance.
Keywords: Athletic performance; Music; Motivation Swimming